PERCEPTIONS OF QUALITY OF LIFE OF SWIMMING PARALYMPIC DISABLED ATHLETES OF THE BEIJING GAMES. (Fiep Bulletin - online, 2011)
This is a descriptive exploratory study with a quantitative approach, which studies about perceptions of quality of life of disabled athletes of the Brazilian Paralympic Swimming. The study was carried out during the Paralympic Games in Beijing in 2008. 14 disabled athletes were surveyed; the collection of data was collected by the using of a structured instrument. Most of the disabled athletes are male, single, aged between 21 and 34 years, white color, borned in Natal, with higher education level, residing in the capital of the states, has health insurance, and minority work. The predominant physical-motor disability, which was the main cause of congenital disease, mostly occurring lesion of the central or peripheral neurological, affecting the lower limbs, most of than walks with or without help. The athletes were evaluated as people with good quality of life, showed their satisfaction with the state of health and said that the pain does not hind the practice of sport, in plus, they said not to have any problem in accept their physical appearance. About the fatigue, they did not complain about it, they are willing, or not have difficulty in physical activity and have good ability in concentration and reasoning. In this sense, we can conclude that disabled athletes have a socio-demographic profile distinctive, as well as consider their quality of life as satisfactory. So we know that the perception of the swimmers put in evidence the importance of practice of physical activities to improve the quality of life, welfare and health of disabled people.
Keywords: quality of life; disabled athletes; swimming